Contraintes et Défis de la Transition Agroécologique Comme Perçus par les Agriculteurs en Tunisie - Souissi, Asma; Dhehibi, Boubaker; Frija, Aymen; Alary, Veronique; Majri, Rihab; Oueslati-Zlaoui, Meriem; Dhraief, Mohamed Zied (International Center for Agricultural Research in the Dry Areas, 2023)
Global food systems are moving away from the goals of sustainable development. In addition to the problems of undernourishment and inequity, these systems contribute to the degradation of natural resources, environmental pollution, and the loss of biodiversity. In this context, several initiatives are being launched by international bodies such as the Food and Agriculture Organisation (FAO) and the Consultative Group for International Agricultural Research (CGIAR) in order to establish more equitable and ecologically, socially, and economically sustainable systems. The agro-ecological transition is seen to change towards sustainable and resilient agricultural systems. However, this transition faces many institutional, social, technical, economic, and environmental obstacles and challenges. The main objective of this study is to determine and understand these obstacles and to identify the factors that inhibit this agro-ecological transition in the Tunisian context. The study is based on the convictions of farmers, who represent not only the first link in the production chain but also the weakest link. The research methodology is based on a participatory approach and qualitative analysis. Focus groups, workshops and an open-ended survey were conducted with farmers in the north-eastern region of Tunisia, where the mixed crop-livestock system is omnipresent. A literature review preceded and accompanied the field study and the analysis of the results. This work was carried out within the framework of the "Agroecology" initiative launched by the CGIAR and implemented in Tunisia by the International Center for Agricultural Research in the Dry Areas (ICARDA). The results of this study reveal many constraints perceived by farmers, mainly related to the climatic conditions, the institutional framework (notably the lack of incentive policies), the lack of financing mechanisms and the complexity of the acceptance and adoption of technical innovations at the farm level (lack of information, failure of extension services, etc.). The results also reveal the importance of using socio-technical systems analysis to better understand and address the root causes behind the issues blocking agro-ecological transitions in Tunisia. This diagnosis contributes to the identification of required actions and to generate the necessary recommendations for decision-makers to stimulate the agro-ecological transition. This communication occurred during the 20th International Scientific Day of INRGREF in Tunis, Tunisia “Sustainable Ecosystem Management for Agroecological Transition and Food Security” (10-11 October 2023).